Towards sturdy and sensable pressure-sensitive adhesive through hierarchical supramolecular interaction - Haohao Lin; Haiming Chen; Jinming Liu; He Li; Dongsheng Mao (Supramolecular Materials, 2023)
Endowing a robust pressure-sensitive adhesive (PSA) with sensable properties is of great significance for in-situ stress detection and information encryption in the fields of electronics, energy storage, flexible sensing, etc. However, it remains great challenge due to the difficulty in balancing interfacial wetting and cohesive strength. Herein, a microphase-separated strategy is proposed to construct an ionogel with a lower modulus of 1.96MPa, a strength of 728kPa as well as a remarkable toughness of 2258.9kJ/m3, which can be used as a sturdy PSA bonded to various substrates (metals, polar plastics, non-polar plastics) under gentle pressure. The comparable modulus and cohesive strength give it an excellent adhesion strength of 1340kPa, which far exceeds most of reported high-performance PSAs. Furthermore, due to the orientation of a large number of ionic groups, the adhesion strength increases by 31.3% once a voltage of 20V is applied. Finally, the sensitive force-resistance response of such PSA that can be used for encrypted messaging was demonstrated.